1,8-Cineole ameliorates right ventricle dysfunction associated with pulmonary arterial hypertension by restoring connexin43 and mitochondrial homeostasis - Jorge M. Alves-Silva; Mónica Zuzarte; Carla Marques; Sofia Viana; Inês Preguiça; Rui Baptista; Cátia Ferreira; Carlos Cavaleiro; Neuza Domingues; Vilma A. Sardão; Paulo J. Oliveira; Flávio Reis; et al. (Elsevier, 2022)
For the first time, the present study unravels a cardiospecific therapeutic approach for Pulmonary Arterial Hypertension (PAH), a disease with a very poor prognosis and high mortality rates due to right ventricle (RV) dysfunction. We first established a new in vitro model of high-pressure-induced hypertrophy that closely resembles heart defects associated with PAH and validated our in vitro findings on a preclinical in vivo model of monocrotaline (MCT)-induced PAH. Our results showed the in vitro antihypertrophic effect of 1,8-cineole, a monoterpene widely found in several essential oils. Also, a decrease in RV hypertrophy and fibrosis, and an improvement in heart function in vivo was observed, when 1,8-cineole was applied topically. Furthermore, 1,8-cineole restored gap junction protein connexin43 distribution at the intercalated disks and mitochondrial functionality, suggesting it may act by preserving cardiac cell-to-cell communication and bioenergetics. Overall, our results point out a promising therapeutic compound that can be easily applied topically, thus paving the way for the development of effective cardiac-specific therapies to greatly improve PAH outcomes.